Dynamic Embeddedness in Chinese Firm Internationalization. (10th April 2017) - Lattemann, Christoph; Alon, Ilan; Spigarelli, Francesca; Marinova, Svetla Trifonova
Abstract : This article presents a multilevel framework to analyze the motivations and location choices of Chinese OFDIs. We contribute to theory‐integration on Chinese OFDI flows and patterns by suggesting a framework that combines country‐, industry‐ and firm‐level analyses and by reflecting aspects from the resource‐based view (firm‐specific advantages), institutional‐based view (push/pull home‐ and host‐country factors), and network‐based view (network relations). We also explicitly incorporate "time" as a variable into our framework by introducing and explaining the concept of dynamic embeddedness as an interaction dimension to reflect the inherent dynamics on all levels and actors. © 2017 Wiley Periodicals, Inc .